Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1681/asn.2018020209
|View full text |Cite
|
Sign up to set email alerts
|

The MEK Inhibitor Trametinib Ameliorates Kidney Fibrosis by Suppressing ERK1/2 and mTORC1 Signaling

Abstract: Background During kidney fibrosis, a hallmark and promoter of CKD (regardless of the underlying renal disorder leading to CKD), the extracellular-regulated kinase 1/2 (ERK1/2) pathway, is activated and has been implicated in the detrimental differentiation and expansion of kidney fibroblasts. An ERK1/2 pathway inhibitor, trametinib, is currently used in the treatment of melanoma, but its efficacy in the setting of CKD and renal fibrosis has not been explored.Methods We investigated whether trametinib has antif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 65 publications
6
64
0
Order By: Relevance
“…Notably, ERK signalling is a prominent feature of tubular epithelial cell injury across a wide range of kidney diseases, with ERK activation in tubular cells correlating with renal dysfunction, interstitial fibrosis and tubular atrophy . Consistent with human studies, there is prominent ERK activation in tubular cells and interstitial fibroblasts in the unilateral ureteric obstruction (UUO) model which correlates with cell proliferation, and a recent study has shown that ERK inhibitor treatment suppressed both cell proliferation and renal fibrosis in the UUO model . Macrophages also play a significant role in the development of renal fibrosis in the UUO model, and activation of PAR2 in human macrophages can induce TNF production …”
supporting
confidence: 57%
See 1 more Smart Citation
“…Notably, ERK signalling is a prominent feature of tubular epithelial cell injury across a wide range of kidney diseases, with ERK activation in tubular cells correlating with renal dysfunction, interstitial fibrosis and tubular atrophy . Consistent with human studies, there is prominent ERK activation in tubular cells and interstitial fibroblasts in the unilateral ureteric obstruction (UUO) model which correlates with cell proliferation, and a recent study has shown that ERK inhibitor treatment suppressed both cell proliferation and renal fibrosis in the UUO model . Macrophages also play a significant role in the development of renal fibrosis in the UUO model, and activation of PAR2 in human macrophages can induce TNF production …”
supporting
confidence: 57%
“…10 Consistent with human studies, there is prominent ERK activation in tubular cells and interstitial fibroblasts in the unilateral ureteric obstruction (UUO) model which correlates with cell proliferation, 11,12 and a recent study has shown that ERK inhibitor treatment suppressed both cell proliferation and renal fibrosis in the UUO model. 13 Macrophages also play a significant role in the development of renal fibrosis in the UUO model, 14 and activation of PAR2 in human macrophages can induce TNF production. 15 This study aimed to define the role of PAR2 in tubular damage, tubulointerstitial inflammation and fibrosis.…”
mentioning
confidence: 99%
“…Similarly, Ruxolitinib treatment inhibited Stat3 and Erk phosphorylation in TGF-β1 -treated NRK-49F cells ( Figure 7C-D). We further analyzed downstream molecules of Jak signaling such as Akt and mTOR which have been shown involved in obstructed kidney [9,10]. Consistent with these reports, UUO kidneys overexpressed Akt, p-Akt, mTOR and p-mTOR.…”
Section: Ruxolitinib Attenuates Akt/mtor/yap Pathwaysupporting
confidence: 71%
“…Our study finally identified that Ruxolitinib treatment attenuated Akt/mTOR pathway. Both mTOR complex 1 (mTORC1) and mTORC2 were activated in UUO kidneys [9,10]. Furthermore, Yap was revealed to mediate mTORC2-induced renal interstitial fibrosis [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation